(untitled) (Bangladesh Journal of Botany, 2026)
The experiment was conducted under normal irrigated and managed stress conditions for morphological and physiological traits to study the genetic potential of 15 rice landraces at vegetative stage for drought tolerance. The highest shoot length was recorded in Mappillai samba at both normal irrigated (58.07 cm) and managed drought stress condition (54.40 cm). The highest leaf length was observed in Nootripathu at normal irrigated (37.60 cm) and managed drought stress (37.03 cm) conditions. More number of tillers was recorded in Norungan both at normal irrigated situation (6.00) as well as drought condition (5.30). Norungan exhibited highest root length in normal irrigated condition (19.00 cm) whereas Kallurundaikar possess lengthy roots at managed stress condition (25.13 cm). Kallurundaikar showed better leaf rolling score (3) and Chithiraikar showed delayed drying symptom than other landraces. Chithiraikar and Norungan have shown higher rate of relative water content (77.0 and 75.3%, respectively) and maximum proline accumulation in Norungan both in normal irrigated (782.3mg/g FW) and managed stress condition (2366.0mg/g FW). Based on the overall performance, the rice landraces Norungan, Kallurundaikar and Chithiraikar can be selected for further breeding programme to obtain new recombinant types for drought tolerance. Bangladesh J. Bot. 55(2): 251-256, 2026 (June)